Answer:
Statement (1) ALONE is sufficient, but statement (2) alone is not sufficient.
Step-by-step explanation:
A multiple of a number is obtained after multiplying the number by an integer.
Here,
x, y are any two integers greater than 1,
(1) We have,
![\small 3y^{2}+7y=x](https://tex.z-dn.net/?f=%5Csmall%203y%5E%7B2%7D%2B7y%3Dx)
![\implies y(3y+7) = x](https://tex.z-dn.net/?f=%5Cimplies%20y%283y%2B7%29%20%3D%20x)
∵ y is an integer ⇒ 3y + 7 is also an integer,
⇒ y × an integer = x
That is, when we multiply y by a number we obtain x,
∴ x is a multiple of y.
Thus, statement (1) ALONE is sufficient.
(2),
![\small x^{2}-x\text{ is a multiple of y}](https://tex.z-dn.net/?f=%20%5Csmall%20x%5E%7B2%7D-x%5Ctext%7B%20is%20a%20multiple%20of%20y%7D)
I.e.
, where a is an integer,
![\implies y\times a = x(x-1)](https://tex.z-dn.net/?f=%5Cimplies%20y%5Ctimes%20a%20%3D%20x%28x-1%29)
∵ x and x - 1 are disjoint numbers,
There are three possible cases,
Case 1 : x is multiple of y
Case 2 : (x-1) is a multiple of y,
Case 3 : neither x nor x - 1 are multiple of y but their product is multiple of y,
Thus, statement (2) is not sufficient.